2017
DOI: 10.1186/s12860-017-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of pericyte smoothened activity in mice with genetic deficiency of leptin

Abstract: BackgroundObesity is associated with multiple diseases, but it is unclear how obesity promotes progressive tissue damage. Recovery from injury requires repair, an energy-expensive process that is coupled to energy availability at the cellular level. The satiety factor, leptin, is a key component of the sensor that matches cellular energy utilization to available energy supplies. Leptin deficiency signals energy depletion, whereas activating the Hedgehog pathway drives energy-consuming activities. Tissue repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Recent studies have associated leptin and LepRb deficiency with pericytopathy in peripheral organs including the liver, pancreas, and bone marrow ( Choi et al, 2010 ; Chien et al, 2016 ; Yue et al, 2016 ; Haley and Lawrence, 2017 ; Xie et al, 2017 ). Using qPCR studies, we further characterized the expression of different leptin receptor isoforms and perivascular markers in the hypothalamus and meninges of LepRb-deficient mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have associated leptin and LepRb deficiency with pericytopathy in peripheral organs including the liver, pancreas, and bone marrow ( Choi et al, 2010 ; Chien et al, 2016 ; Yue et al, 2016 ; Haley and Lawrence, 2017 ; Xie et al, 2017 ). Using qPCR studies, we further characterized the expression of different leptin receptor isoforms and perivascular markers in the hypothalamus and meninges of LepRb-deficient mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore tempting to speculate that leptin signaling may also play a role in brain diseases with an inflammatory component, perhaps via the regulation of the perivascular coverage and leukocyte infiltration. Lastly, several studies reported peripheral pericyte loss in mice deficient for leptin or LepRb ( Chien et al, 2016 ; Haley and Lawrence, 2017 ; Xie et al, 2017 ), and further demonstrated that LepRb signaling played an important role in the proliferation and differentiation of peripheral pericytes ( Saxena et al, 2002 ; Choi et al, 2010 ; Zhou et al, 2014 ; Yue et al, 2016 ). This suggests that intact LepRb signaling is required for normal perivascular cells activities.…”
Section: Discussionmentioning
confidence: 95%
“…This increase in fibrosis leads to complications in adipose tissue such as high extracellular matrix rigidity and reduced expandability. It also induces ectopic lipid deposition, which leads to insulin resistance and impairment of metabolic pathways ( Xie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study (11) defined the in situ impairment by a systemic or local noxious milieu in the tissue of origin, particularly long-term uncontrolled-type 2 diabetes (UC-T2D) and obesity in a rat model, and showed that in addition to their phenotype imprinting, these stem cells had lost the capacity to exert tissue and functional repair when implanted into another tissue damaged by the same environment in either syngenic or autologous hosts. There are some reports describing deleterious effects of the T2D milieu and its associated oxidative stress on the microenvironment impairing stem cells, inducing apoptosis, interfering with wound healing capacity, and other effects (e.g., 1215), as well as obesity per se or associated with diabetes on the number of stem cells and progenitor cells, their lifespan, and other effects (e.g., 1618). The impairment of stem cells was ascribed in some cases to dyslipidemia (e.g., 19, 20).…”
Section: Introductionmentioning
confidence: 99%